Shadowheart - Alioto, Dean.; MacFadyen, Angus; Ament, Justin; Baldwin, Daniel; Sadler, William; Desert Moon Pictures..; Indiesyndicate Productions; Anchor Bay Entertainment, Inc. (Troy, MI : Distributed by Anchor Bay Entertainment, 2009)
"He came for revenge ...he found redemption.
Title from container.
DVD; Dolby surrounf 5.1.
Angus MacFadyen, Justin Ament, Daniel Baldwin, William Sadler.
Originally released as a motion picture in 2008.
Features include audio commentary with co-writer/director ; behind the scenes of Shadowheart ; trailor.
Rated PG-13, for some intense western violence.
Keywords: Murder -- Drama; Feature films; Western films